Barriers to Access Health Care Services among Rural Adolescent Girls in Raina I Block, Purba Bardhaman, West Bengal - Mousumi Dholey (ACCB Publishing, 2021)
Adolescence in girls is a crucial transition phase during which they experience biological and psychological changes along with changes in social outlook. This phase provides an opportunity to lay the foundation for their future health. But, in rural areas, adolescent girls are often deprived of better nutrition and proper health care guide, resulting in serious health issues like malnutrition, stunting, wasting, and anaemia. Moreover, their access to health care services is subjected to various constraints as infrastructural and societal barriers such as regressive norms, social stigma, gendered family structure, etc. Thus, the present study attempts to explore the perceived barriers that prevent rural adolescent girls from accessing health care services at the micro-level. A community-based cross-sectional study was carried out after randomly selecting 120 adolescent girls in the age cohort of 10-19 years in the Raina-I block of Purba Bardhaman district. The results suggested that societal barriers have a significant influence over health-related decision-making. Besides, lack of quality health care services and economic burden are some of the other significant obstacles observed here.